If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9u + -7 = 3u + 5 Reorder the terms: -7 + 9u = 3u + 5 Reorder the terms: -7 + 9u = 5 + 3u Solving -7 + 9u = 5 + 3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3u' to each side of the equation. -7 + 9u + -3u = 5 + 3u + -3u Combine like terms: 9u + -3u = 6u -7 + 6u = 5 + 3u + -3u Combine like terms: 3u + -3u = 0 -7 + 6u = 5 + 0 -7 + 6u = 5 Add '7' to each side of the equation. -7 + 7 + 6u = 5 + 7 Combine like terms: -7 + 7 = 0 0 + 6u = 5 + 7 6u = 5 + 7 Combine like terms: 5 + 7 = 12 6u = 12 Divide each side by '6'. u = 2 Simplifying u = 2
| 3ln(3x-4)=8 | | -3-y=1 | | -3-7=1 | | 4x^3-6=0 | | -4g=-5g-4 | | 4/5-1/5=2/5n | | 4/5-1/5=2/5 | | 2d^2-6d=10 | | (4z+6)+x+2y+106=180 | | V^2=-54 | | -3+8r=9r | | 0.2(1.2x-9)+5=9.8 | | -4d=-3d-9 | | x*0.28=1015 | | 3x^3(4x^4+172)= | | 7n^2=4n-4 | | p=5w+5l | | 8(5x)=(8*5)x | | -(-3)[(6)-(-3)]= | | -10f=-9f-8 | | 8a+12=-3+34 | | 3x^2-15=66 | | 3x^3(4x^4+172)=0 | | 2(3X+5)=4X-4 | | 3+m=15-5m | | -16t^2+96t+64=0 | | 16x^2-256x-25Y^2-150y+399=0 | | 9(e-1)=-7e-9 | | (2x+9)-5=0 | | 2+2x+2=14 | | -p^2-5p+16=0 | | 1/8z=7 |